DEBT FORGIVENESS PRINCIPLE IN BUSINESS LEGAL REPRESENTATIVES - Pebry Dirgantara (Warmadewa Press, 2019)
The aims of this research is on the form of engagement between bankrupt debtors on the remaining debt that has not been paid to creditors based on PKPU UUK and the form of debt forgiveness principles as a form of business legal renewal, especially regarding the debtor's liability to the remaining debt to its creditors. The methods of this research is uses 3 (three) sources of legal material, namely primary legal materials, secondary legal materials, and tertiary legal materials. The primary legal material obtained from the field is first examined for completeness and clarity to be classified as well as systematic and consistent preparation to facilitate analysis. Secondary legal materials obtained from the literature are selected and collected systematically, so that they can be used as a reference in conducting analysis. From the results of the legal material of library research and the field, a descriptive analytical discussion was conducted. The result of research found Based on the bankruptcy settlement stipulated in the PKPU UUK, it can be seen that with the existence of a bankrupt decision against a debtor, in which the settlement still leaves the remainder of the debt, the agreement between the debtor and his creditors will not end or break before the debt is repaid and The existence of the debt forgiveness principle characterizes that in a business can not be separated from a risk and / or uncertainty and all things that have the potential to harm the business and can even bankrupt the legal subject business.